Empowering leadership and occupational burnout: the moderated mediation model - Hira Salahuddin Khan; Muhammad Salman Chughtai; Ma Zhiqiang (BMC Psychology)
Abstract Background This study examines the impact of empowering leadership on occupational burnout through the mediating role of workaholism and the moderating effect of psychological hardiness in the relationship between empowering leadership and occupational burnout. The present study employs empowerment and hardiness theory. Further, the moderated mediation hypothesis was also investigated. Methods Survey responses from 212 permanent employees (nurses) in the healthcare industry were gathered using the temporal separation (two time-lags with one month between the first and second lags) to test the proposed hypotheses. Different statistical analysis techniques, confirmatory factor analysis, discriminant and convergent validity and PROCES-macro were used. Results The current study findings shows that empowering leadership significantly reduces occupational burnout. Furthermore, the results of the study confirm that workaholism plays a crucial role as a mediator between empowering leadership and occupational burnout in the workplace. Additionally, the findings shows that empowering leadership burdens nurses by making them work excessively, which causes occupational burnout in the workplace. Furthermore, psychological hardiness is a significant moderator in the relationship between workaholism and occupational burnout. Finally, the moderated mediation model results showed that nurses with high psychological hardiness adjust and manage well with intense workloads, i.e., workaholism, when emboldened through their leaders which leads to reduction in occupational burnout. Conclusion/Implications The findings emphasize the potential advantages and hazards of empowering leadership in the nursing profession and the management of healthcare. This study builds on earlier research by empirically investigating how workaholism and psychological hardiness influence the relationship between empowering leadership and occupational burnout in the nursing profession of Pakistan.